A Critical Review of Capital Structure Theories - Javed, Syed Muhammad; ., Agha Jahanzeb; ., Saif-ur-Rehman (Information Management and Business Review, 2012)
The purpose of this paper is to scrutinize and appreciate the theories of capital structure starting from theory of Miller and Modigliani (1958) of capital structure, which is also known as irrelevance theory of capital structure and also including theory like pecking order theory, trade off theory, market timing theory and agency cost theory. In addition, authors have tried to explain the theories and their contradiction with each other in detail. This paper will be an addition to understand the theories of capital structure.